Beautiful boys - Block, Francesca Lia 1962- (HarperCollins, 2004)
Two darkly magical Weetzie Bat stories about the search for self from Francesca Lia Block, Missing Angel Juan and Baby Be-Bop. Features two tales in which the ghosts of dead relatives intervene to offer strength and courage to a young girl in New York trying to rescue a boy in trouble and a sixteen-year-old boy in Los Angeles coming to terms with being gay.
New edition of two novels previously published separately: New York : Harper Collins, 1993 and 1995, respectively
Enth.: Missing Angel Juan. Baby be-bop
Keywords: Ghosts / Fiction; Homosexuality / Fiction; Ghost stories; Homosexuality / Juvenile fiction; Los Angeles (Calif.) / Fiction; New York (N.Y.) / Fiction; Los Angeles (Calif.) / Juvenile fiction; New York (N.Y.) / Juvenile fiction